Minangkabau Tribal Asset Management in Amlak Shirkah for Migrant Tribe Members from the Perspective Fiqh Muamalah - Arianti, Farida; Willya, Evra; Husni, Alfi; Zulkifli; Zulfikor; Alfitri, Aulia (Al-Mazaahib: Jurnal Perbandingan Hukum, 2025)
This study discusses the ownership system and management of joint assets for clan members who are abroad. According to the Minangkabau Matrilineal tradition, each clan member has the right to own and manage joint assets, but the rights of migrants as one of its members are still unclear in terms of joint ownership boundaries and tend to be objects of dispute. This research is a qualitative with a phenomenological approach in the realm of Minangkabau customs, especially the Tigo Balai Nagari. Primary data sources from members of the tribe who have the right to hold customary land, as well as to the tribal grandfather/mamak who controls customary land. Secondary sources are the nagari community around the village where the object of research is. This Article uses in-depth interviews with interview guidelines, while the key instrument is the researcher himself. Then we use observation techniques to guide data acquisition. Data validity technique by triangulation of sources. Qualitative descriptive data analysis technique. The results found that clan members who are abroad still have ownership rights to the joint property as long as they are still members of the clan or tribe, while regarding the management rights only to their sisters who are in their hometowns. The conclusion is that joint ownership in the Minangkabau customary perspective has the same right to manage the joint property. In terms of fiqh muamalah, shirkah property only applies to management and can be transferred, especially in the management only in the name of the migrant clan member. Penelitian ini membahas tentang sistem kepemilikan serta pengelolaan harta bersama bagi anggota klan yang berada di perantauan. Secara adat Matrilineal Minangkabau, setiap anggota klan memiliki hak untuk memiliki dan menggelola harta bersama namun hak perantau sebagai salah satu anggotanya masih belum ditemui titik terangnya secara batas kepemilikan bersama dan cendrung menjadi objek yang dipertikaian. Artikel ini adalah penelitian kualitatif dengan pendekatan fenomenologi di ranah adat Minangkabau, khususnya Nagari Tigo Balai. Sumber data primer dari anggota kaum suku yang memiliki hak pemegang tanah ulayat, serta kepada datuk/mamak suku di Nagari. Sumber sekunder berupa masyarakat nagari di sekitar perkampungan di tempat objek penelitian. Teknik pengambilan data menggunakan wawancara mendalam dengan alat pedoman wawancara, sedangkan instrument kunci adalah peneliti sendiri. Kemudian menggunakan teknik observasi dalam memandu perolehan data. Teknik keabsahan data secara trianggulasi sumber. Teknik analisis data secara deskriptif kualitatif. Hasil yang ditemukan bahwa para anggota klan yang berada di perantauan tetap memiliki hak milik terhadap harta bersama tersebut sepanjang mereka masih menjadi anggota klan atau suku, sedangkan mengenai hak pengelolaannya hanya pada saudarinya yang berada di kampung halaman. Kesimpulannya bahwa kepemilikan bersama dalam prespektif adat Minangkabau sama-sama berhak untuk mengolah harta bersama tersebut. Secara fikih muamalah, harta shirkah hanya berlaku pada pengelolaan saja serta dapat dipindahtangankan khususnya pada pengelolaanya saja atas nama perantau.